BCI-Controlled Wheelchair; Audio-Cue Motor Imagery-Based Paradigm - Velasco-Álvarez, Francisco Javier; Varona-Moya, Sergio; Blanca-Mena, María José; Sancha-Ros, Salvador; Ron-Angevin, Ricardo (My University, 2014)
In this study we present a control paradigm that enables subjects to drive a real wheelchair using four navigation commands. The control is achieved through the discrimination of two mental tasks (relaxed state versus one active Motor imaagery task), in order to reduce the risk of misclassification. After a short training, the paradigm becomes only audio-cued, thus avoiding the need of a graphical interface that could distract subjects’ attention.
Keywords: Interacción hombre-ordenador; Interfaces de ordenadores; Brain Computer Interface (BCI); Imagery motor; Wheelchair